2007
DOI: 10.1007/s00248-006-9179-9
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Mycoflora of Bark, Leaf, and Stem Tissues of Azadirachta indica A. Juss (Neem) from Varanasi (India)

Abstract: A systematic study was made of the endophytes of Azadirachta indica A. Juss (the neem tree) growing in several of its natural habitats in India. A total of 233 isolates of endophytic fungi representing 18 fungal taxa were obtained from segments of bark, stem, and leaves of this tree. Hyphomycetes (62.2%) were the most prevalent followed by the Coelomycetes (27.4%) and Mycelia Sterilia (7.7%). As mathematically determined, the maximum species richness and frequency of colonization of endophytes appeared in leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 41 publications
12
113
1
2
Order By: Relevance
“…This particular strain was isolated from leaf tissues of P. longum and was recorded as an incidental rare strain (1/42 isolates). Members of Periconia have a very wide host range as an endophyte and have been reported from several other pharmaceutically important plants, such as Azadirachta indica, 33 Eucalyptus citriodora, 44 Torriya grandifolia etc. 45 The SEM study of this strain showed very prominent characteristic long conidiophores, dark, long, stout and shortly branched near the apex, bearing attached groups of conidiogenous cells at their tips (Figures 1a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular strain was isolated from leaf tissues of P. longum and was recorded as an incidental rare strain (1/42 isolates). Members of Periconia have a very wide host range as an endophyte and have been reported from several other pharmaceutically important plants, such as Azadirachta indica, 33 Eucalyptus citriodora, 44 Torriya grandifolia etc. 45 The SEM study of this strain showed very prominent characteristic long conidiophores, dark, long, stout and shortly branched near the apex, bearing attached groups of conidiogenous cells at their tips (Figures 1a and b).…”
Section: Resultsmentioning
confidence: 99%
“…All sample tissues were then placed onto separate petri dishes (60 mm) containing potato dextrose agar supplemented with 250 mg l À1 oxytetracycline hydrochloride (Terramycin, Pfizer, Mumbai, India) for isolating endophytic fungi, 33 34 and nutrient agar for isolating endophytic bacteria. All petri dishes were sealed with sterile parafilm to protect them from contamination during repeated handling while examining endophytes, and from desiccation.…”
Section: Surface Treatment Isolation and Culture Conditionsmentioning
confidence: 99%
“…The research on endophytic fungi and their huge diversity among plants has a long history. Recently it has been reported that each plant harbour one or more endophytic fungi (Verma et al, 2007;Kharwar et al, 2008). These endophytic fungi are an outstanding source of secondary metabolites which possess variety of bioactive potential.…”
Section: Diversity Of Endophytic Fungi and Their Functional Rolesmentioning
confidence: 99%
“…Isolation and preliminary screening of endophytes Surface treatment was performed by sequential dipping into 70 % ethanol for 1 min, 5 % NaOCl for 5 min, 96 % ethanol for 0.5 min, followed by three rinses in sterile distilled water as previously established method (Verma et al 2007(Verma et al , 2009a(Verma et al , 2011. All tissues were then placed onto separate petri dishes (60 mm) containing potato dextrose agar (PDA, Himedia, Mumbai) supplemented with 250 mg l -1 oxytetracycline hydrochloride (Terramycin, Pfizer) for isolating endophytic fungi.…”
Section: Plant Samplesmentioning
confidence: 99%